Chirurgie und Management: natürliche Partner - Bork, Ulrich; Koch, Moritz; Büchler, Markus W.; Weitz, Jürgen (Der Chirurg, 2012)
The term management is a description of the functions: planning, organization, leadership and control in institutions and the corresponding persons holding these powers. In order to efficiently lead a department of surgery, surgeons need to possess management qualities and have to be able to act as team leaders. Good management of a surgical department leads to avoidance of complications and increased profits as well as more efficient use of operating room capacities and a better organization within the department.
Gesehen am 23.04.2018